Trading Mechanisms, Return’s Volatility, and Efficiency in the Casablance Stock Exchange - Ferrouhi, El Mehdi; Ezzahid, Elhadj (The Indonesian Capital Market Review, 2013)
This paper studies the impact of the stock market continuity on the returns volatility and on the market efficiency in the Casablanca Stock Exchange. For the most active stocks, the trading mechanism used is the continuous market which is preceded by a call market pre opening session. Results obtained concerning return volatility and efficiency under the two trading mechanisms show that the continuous market returns are more volatile than the call market returns and 50% of stocks studied show independence between variations.